Un patrimoine redécouvert : les dépôts du Centre national des arts plastiques à l’École nationale supérieure des beaux-arts de Paris (1809-1923) - Stéphane Allavena (In Situ)
The Centre national des Arts plastiques, the national centre for the plastic arts, is the heir to a service of fine arts, sciences and theatre first created in 1791 in order to support artistic creation. In 1996, the Centre undertook a retrospective inventory of all the works of art commissioned and purchased by the State since the French Revolution. The part of the inventory carried out at the École nationale supérieure des Beaux-Arts (ENSBA), the Paris fine arts school, permitted the identification of a remarkably diversified collection of about 15,000 items which were deposited at this school, intended principally for the ‘study museum’, officially founded on 17 September 1834, or the reserve collections of the library, opened in 1863. By a close examination of the archives left by the fine arts administration and by the administration of the school itself (series F 21 and AJ 52 at the national archives), we were able to show how these deposits were closely related to the pedagogical and institutional evolutions of the school. Illustrations of this conclusion are to be seen in the number of models and plaster casts given to the school during the neo-classical period, the number of copies of paintings during the Second Empire—the logical consequence of the creation of painting ateliers in 1863—or the number of ornamental drawings during the Third Republic, destined to accompany the new courses in the decorative arts.